Targeted cell delivery of mesenchymal stem cell therapy for cardiovascular disease applications: a review of preclinical advancements - Huerta, Carlos Theodore; Voza, Francesca A.; Ortiz, Yulexi Y.; Liu, Zhao-Jun; Velazquez, Omaida C. (Frontiers in Cardiovascular Medicine, 2023)
Cardiovascular diseases (CVD) continue to be the leading cause of morbidity and mortality globally and claim the lives of over 17 million people annually. Current management of CVD includes risk factor modification and preventative strategies including dietary and lifestyle changes, smoking cessation, medical management of hypertension and cholesterol lipid levels, and even surgical revascularization procedures if needed. Although these strategies have shown therapeutic efficacy in reducing major adverse cardiovascular events such as heart attack, stroke, symptoms of chronic limb-threatening ischemia (CLTI), and major limb amputation significant compliance by patients and caregivers is required and off-target effects from systemic medications can still result in organ dysfunction. Stem cell therapy holds major potential for CVD applications but is limited by the low quantities of cells that are able to traffic to and engraft at diseased tissue sites. New preclinical investigations have been undertaken to modify mesenchymal stem cells (MSCs) to achieve targeted cell delivery after systemic administration.Although previous reviews have focused broadly on the modification of MSCs for numerous local or intracoronary administration strategies, here we review recent preclinical advances related to overcoming challenges imposed by the high velocity and dynamic flow of the circulatory system to specifically deliver MSCs to ischemic cardiac and peripheral tissue sites. Many of these technologies can also be applied for the targeted delivery of other types of therapeutic cells for treating various diseases.